(3cJGH aj GdWHs - (3EHQGgje GdNGRfs ((3LHd dHfGf s)
(3ChdgG (B:s
(3GdMeO ddg GdPi QHi YbhdfG hHYO adeG cGf Yde GdWH Yde dGjOQc dg bQGQG Cf jQJH gPG GdcJGH Ydi ebGdGJ haUhd hCHhGH GdcJGH GdChd ai bhGfjf GdCeQGV s
(3BNQgG (B:s
(3OQge GdTQHI ef OQge Edi OQgejf hEPG TQH CcKQ ef Pdc cGf UGHkG Je HYhf Gddg JYGdi s
(3GdfSNI HgG MhGTs
(3cJHJ HYV GdcdeGJ HGdMeQIs
(3HBNQg agQS GdcJGHs
(3JHUQGJ GdCUd (B:s
(3MGdI GdfSNI LjOI s
(3GdfSNI HgG CQVg s
Keywords: (3GdWHs